The Adventurous Girl's Handbook : For Ages 9 to 99 - Edited by Brennan, Stephan and Brennan, Lara (New York Skyhorse Publishing, 2009)
A compendium of tips and advice for girls, including topics as diverse as interior decoration, outdoor skills, sports, arts and crafts, baking, self-defense, and mental and physical health.
Include Appendix
Keywords: Recreation -- Girls -- Handicraft for girls